2009
DOI: 10.1111/j.1471-4159.2009.06032.x
|View full text |Cite
|
Sign up to set email alerts
|

A constitutively active form of neurokinin 1 receptor and neurokinin 1 receptor‐mediated apoptosis in glioblastomas

Abstract: Previous studies have shown that neurokinin 1 receptor (NK1R) occurs naturally in human glioblastomas and its stimulation causes cell proliferation. In the present study we show that stimulation of NK1R in human U373 glioblastoma cells by substance P increases Akt phosphorylation by 2.5‐fold, with an EC50 of 57 nM. Blockade of NK1R lowers basal phosphorylation of Akt, indicating the presence of a constitutively active form of NK1R; similar results are seen in U251 MG and DBTRG‐05 glioblastoma cells. Linkage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
79
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 41 publications
3
79
0
Order By: Relevance
“…The protective effects of SP on g-irradiation-damaged stem cells suggest that SP might be an important tool for the radiation recovery of the bone marrow. The protective effects of SP on apoptosis have been reported in other types of cells (Amadoro et al, 2007;Koon et al, 2007;Akazawa et al, 2009;Kang et al, 2009), but this is the first study to examine BMSCs. Future work should vary the number of and intervals between SP injections to identify the maximum protective effect afforded by SP to damaged cells.…”
Section: Discussionmentioning
confidence: 92%
“…The protective effects of SP on g-irradiation-damaged stem cells suggest that SP might be an important tool for the radiation recovery of the bone marrow. The protective effects of SP on apoptosis have been reported in other types of cells (Amadoro et al, 2007;Koon et al, 2007;Akazawa et al, 2009;Kang et al, 2009), but this is the first study to examine BMSCs. Future work should vary the number of and intervals between SP injections to identify the maximum protective effect afforded by SP to damaged cells.…”
Section: Discussionmentioning
confidence: 92%
“…For example, the alteration of the IP3K/Akt pathway was reported to regulate the migration and invasion of human glioma cells LN229, T89G, and U-373 through the reduction of MMP-2 and MT1-MMP (43). NK1R activation was verified to induce MAPK and Akt activation, mediating cell proliferation and the anti-apoptosis effect in glioma cells and other tumor cells (15,16,21). In this study, we proved the following in U-251 cells: 1) that NK1R activation by hHK-1 stimulated intracellular calcium release and the phosphorylation of ERK, JNK, and Akt through the G q -PLC pathway; 2) that activation of these kinases was related to the up-regulation of MMP-2 and MT1-MMP expression and the promotion of cell migration induced by hHK-1.…”
Section: Discussionmentioning
confidence: 99%
“…NK1R was also detected in many established glioma cell lines, such as U-251 MG, U-87 MG, DBTRG-05 MG, and SNB-19 (12)(13)(14), which were often used as the natural models to investigate NK1R biological functions. It was reported that NK1R activation induced the phosphorylation of Akt and mitogen-activated protein kinase (MAPK) family members (15)(16)(17), which subsequently stimulated different transcription factor activities to adjust target gene expression (18 -20). These regulatory mechanisms were engaged by NK1R to stimulate DNA synthesis and cytokine secretion and to mediate the anti-apoptosis effect (15,16,18,21).…”
mentioning
confidence: 99%
See 2 more Smart Citations